DONOR DARAH SAAT PANDEMI COVID-19 - Attisya Milenty Putri Djuardi (Jurnal Medika Hutama, 2020)
COVID-19 is the new type of severe pneumonia caused by the SARS-CoV-2 virus. The spread of this virus occurs rapidly and WHO has been labelled the SARS-CoV-2 outbreak as a pandemic. The positive cases of COVID-19 is increasing everyday and giving negative impacts to various sectors including the health sector. One of the impacts that occur in the health sector is the lack of blood supply in blood bank. The lack of blood supply caused an imbalance between the higher demand compared to the blood supply. This article was written with purpose of knowing the impact of the COVID-19 pandemic on blood supply in various countries including Indonesia. The method used was literature review of 16 NCBI, Google Scholar and news articles from 2016-2020. The analytical method used was systematic literature review by identifying, assessing, evaluating, and developing research with a relevant topic focus. The result of this literature review showed that the amount of blood supply has been decreased drastically since the COVID-19 pandemic started and it happened because people are worried that they will be infected by COVID-19 when they donors their blood.